(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Even if many other elements of the evolution process are important, man is the central one. Theactions, controls, and aims of man lead other variables in the appropriate paths. The progress isinfluenced by his level of education, intensity of effort, energy, quality, value, skill, and knowledge. As aresult, cultivating one’s own people is crucial to a country’s progress. Education may be defined as theprocess through which a group of individuals acquire information, skill, value, belief, and habit via themediums of group discussion, instruction, and study. A powerful country, self-sufficient in economics,non-corrupt in character, and scientifically-minded, may be built on a foundation of education, which is asocial process responsible for influencing the collective behavior of individuals.Human resourcemanagement (HRM) is essential to the success of educational institutions if they are to achieve theirdeclared missions and objectives.